2009
DOI: 10.1002/smll.200800926
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Nanoparticles for Reducing Hemolytic Activity Towards Mammalian Red Blood Cells

Abstract: The hemolytic properties of amorphous silica and MCM‐41‐type mesoporous silica nanoparticles (MSNs) with rabbit red blood cells (RBCs) are compared. The amorphous silica exhibits a high hemolytic activity toward the RBCs. In contrast, a high biocompatibility between the MSNs and the RBCs is observed. The low hemolytic activity of the MSNs offers promising potential for various in vivo biotechnological applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
424
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 516 publications
(442 citation statements)
references
References 31 publications
14
424
4
Order By: Relevance
“…30 These results were later confirmed by Lin and Haynes, who demonstrated that the hemocompatibility of MSNs also depended on the size of the nanoparticles. 31 These findings were mainly based on hemolysis assays performed by UV-vis spectroscopy.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…30 These results were later confirmed by Lin and Haynes, who demonstrated that the hemocompatibility of MSNs also depended on the size of the nanoparticles. 31 These findings were mainly based on hemolysis assays performed by UV-vis spectroscopy.…”
mentioning
confidence: 66%
“…[43][44][45][46][47] The occurrence of the interaction depends on whether the amount of energy released from the binding of the MSNs with the RBC membrane (E i ) is able to overcome the amount of free energy required to bend the membrane and adapt to the surface of MSNs (E b ). The former energy is associated with the external surface area (i.e., accessible silanols) of MSN, 30 while the latter is proportional to the curvature or inversely proportional to the square of the radius (r) of the particle. 43,44,47 The external surface areas of s-MSNs and l-MSNs, calculated from the t plots of their N 2 adsorption isotherms, 48 were 81.6 and 155.4 m 2 g -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…13,29 As the hemolytic effect of negatively charged silica was practically the same when samples were normalized by specific surface area, it is possible to conclude that not only the negative zeta potential must be considered as the responsible for the citotoxicity of the nanoparticles, once sample Si-P(CH 3 )O 3 H possesses a more negatively charged surface. In this way, other mechanisms and interactions such as ROS, hydrogen bonds and van der Waals forces must be considered as responsible for the citotoxicity observed here.…”
Section: Resultsmentioning
confidence: 96%
“…Firstly, it was observed that silanol groups on mesoporous silica structures induce less hemolytic effect compared to rigid spherical nanoparticles possibly due to shape-induced effects, which determine the spatial availability of silanols on the nanoparticle-cell interface. 13 Further, it was observed that: (i) smaller Stöber silica nanoparticles (24 nm) induce a pronounced hemolytic effect when compared with bigger ones (263 nm); 14 (ii) nanostructures with high aspect ratio (nanorods) are more cytotoxic than spherical nanoparticles; 15 (iii) mesoporous silica nanostructures (MSNs) with ordered pores (MCM-41) induce a stronger hemolytic effect compared with non-ordered; 14 (iv) small mesoporous nanoparticles (20 nm) consisted of ethenylenebridged silsesquioxane present very low toxicity 16 and (v) polymers such as PEG (polyethylene glycol) can be used to coat particles in order to greatly reduce the hemolysis. 17 Furthermore, an extensive assessment of the interaction of bare and functionalized porous silica nanomaterials with RBCs concluded that SBA-15-type MSNs cause the deformation of RBCs and consequently lead to their disruption.…”
Section: Introductionmentioning
confidence: 99%
“…The biocompatibility of MSN both in vitro and in vivo has been demonstrated by several recent studies. [4][5][6][7] Furthermore, literature reports on the biodistribution and circulation properties of MSN administered in animals by intravenous injection have highlighted the promising potential of these multifunctional nanoparticles for in vivo biomedical applications and organ-specific delivery of therapeutics.…”
mentioning
confidence: 99%